Optimizing acyclic traffic signal switching sequences through an Extended Linear Complementarity Problem formulation - De Schutter, Bart (European journal of operational research, 2002)
In this paper we first show how the Extended Linear Complementarity Problem, which is a mathematical programming problem, can be used to design optimal switching schemes for a class of switched systems with linear dynamics subject to saturation. More specifically, we consider the determination of the optimal switching time instants (the switching sequences are acyclic, but the phase sequence is pre-fixed). Although this method yields globally optimal switching time sequences, it is not feasible in practice due to its computational complexity. Therefore, we also discuss some approximations that lead to suboptimal switching time sequences that can be computed very efficiently and for which the value of the objective function is close to the global optimum. Finally we use these results to design optimal switching time sequences for a traffic signal controlled intersection so as to minimize criteria such as average queue length, worst case queue length, average waiting time, and so on.